Listening to voices from multiple sources: A qualitative text analysis of the emotional experiences of women living with breast cancer in China - Li, Chaixiu; Ure, Cathy; Zheng, Wanting; Zheng, Chunrao; Liu, Jianhong; Zhou, Chunlan; Jian, Biao; Sun, Lijun; Li, Wenji; Xie, Lijun; Mai, Yuchang; Zhao, Huihui; et al. (Frontiers in Public Health, 2023)
Background: Receiving a breast cancer diagnosis and treatment is both a physical and emotional journey. Previous studies using single source data have revealed common and culture-specific emotional experiences of patients living with breast cancer. However, few studies have combined such data from multiple sources. Thus, the current study sought to explore the emotional experiences of women in China newly diagnosed, postoperatively or while undergoing chemotherapy using a variety of data sources. We posited that even though women living with breast cancer in China have multiple channels through which they can express these emotional experiences, little variance would be found in their emotional expressivity and themes they want to express due to cultural inhibitions. Methods: Text data from female patients newly diagnosed, postoperatively or while undergoing chemotherapy were collected between June 2021 and January 2022 via Python web crawler, semi-structured interviews, and an expressive writing intervention. Data were transcribed and subjected to thematic analysis. Reporting followed the consolidated criteria for reporting qualitative studies (COREQ) guidelines. Results: Analyses were based on 5,675 Weibo posts and comments published by 448 posters and 1,842 commenters, transcription texts from 17 semi-structured interviews, and 150 expressive writing texts. From this total collection of 461,348 Chinese characters, three major themes emerged: i) conflicting emotions after diagnosis; ii) long-term suffering and treatment concerns, and iii) benefit finding and cognitive reappraisal. Conclusions: Despite gathering information from various sources, we found that distress from body image disturbances, female role loss and conflict, and changes in sexuality and fertility, were consistent among this sample of female Chinese patients with breast cancer. However, when women engaged actively in benefit finding and cognitive reappraisal with strong social support, patients were able to find ways to adapt and reported post-traumatic growth. Strong social support was an important facilitator in this growth. These study findings emphasize that healthcare professionals ought to increase the cultural sensitivity, provide multiple channels to encourage patients to express their emotions, and incorporate the screening for patient emotional distress at all diagnostic and treatment phases into part of routine nursing care.